Cognate MHC-TCR interaction leads to apoptosis of antigen-presenting cells. - Setterblad, N; Blancheteau, V; Delaguillaumie, A; Michel, F; Bécart, S; Lombardi, G; Acuto, O; Charron, D; Mooney, N (2004)
Antigen presentation to T lymphocytes has been characterized extensively in terms of T lymphocyte activation and eventual cell death. In contrast, little is known about the consequences of antigen presentation for the antigen-presenting cell (APC). We have determined the outcome of major histocompatibility complex class II-restricted peptide presentation to a specific T cell. We demonstrate that specific T lymphocyte interaction with peptide-presenting APCs led to apoptosis in the APC population. In contrast, T lymphocyte interaction with nonpeptide-loaded APCs or APCs loaded with monosubstituted peptide failed to induce T lymphocyte secretion of interleukin-2 and APC apoptosis. Phosphatidylserine externalization and mitochondrial depolarization were used to evaluate APC apoptosis. Fas/Fas ligand interactions were not required, but cytoskeletal integrity and caspase activation were essential for APC apoptosis. Antigen presentation leading to T lymphocyte activation is therefore coordinated with apoptosis in the APC population and could provide a mechanism of immune response regulation by eliminating APCs, which have fulfilled their role as specific ligands for T lymphocyte activation. This pathway may have particular importance for APCs, which are not sensitive to death receptor-induced apoptosis.